Alternative Dispute Resolution in Civil Cases : Trends, Benefits, and Legal Implications - Melda Ayu Nengsi; Thalia Widia Ramadanti (Green Social: International Journal of Law and Civil Affairs, 2024)
This paper investigates the rising trend of alternative dispute resolution (ADR) methods in civil cases, analyzing their benefits and legal implications. With increasing caseloads in courts, ADR provides a viable alternative for efficient dispute resolution. The study evaluates various ADR methods, including mediation and arbitration, and examines their impact on the legal system, accessibility to justice, and cost-effectiveness. Findings suggest that ADR can significantly reduce litigation costs and improve outcomes for all parties involved, while also raising questions about enforceability and procedural fairness.